Evaluating experimental drill on deployment of military emergency medical team for disaster relief - Luong, Trung Hieu; Nguyen, Nhu Lam; Hoang, Hai; Nguyen, Tien Dung; Tran, Dinh Hung; Ngo, Minh Duc; Nguyen, Dai; Nguyen, Thanh Chung; Le, Quang Thao; Nguyen, Thai Ngoc Minh (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: To evaluate the results of implementing the Military Medical Team model for natural disasters. Subjects and methods: Organizing an experimental drill of simulated earthquake situations with 25 trauma victims and 5 cases of chronic illness. The evaluated content included the implementation of military medical stations and Medical response at military medical stations in terms of admission, triage, emergency care, and transferring. Results: The deployment of the military medical station for disaster relief met the requirements of over 80%. The management of the team leaders, the members’ activities, proficiency in using equipment and forms, as well as coordination were sufficient > 95%. The triage results using START met the scenario requirements from 87.5% and over. All contents of operation achieved 90% or more. Conclusion: The drill met the set requirements; some contents were added to complete the model.